Self-reported health, lifestyle and social circumstances of Australian adult cancer survivors: A propensity score weighted cross-sectional study. (August 2020) - Tran, Bich; Vajdic, Claire M.; Webber, Kate; Laaksonen, Maarit A.; Stavrou, Efty P.; Tiller, Kerry; Suchy, Sue; Bosco, Ann Marie; Harris, Mark F.; Lloyd, Andrew R.; Goldstein, David
Highlights: Compared to those with no cancer history, cancer survivors reported markedly poorer health. They also reported greater limitations in their ability to perform every-day activities. Cancer survivors were also less likely to work, volunteer and go outdoors. These inequalities were evident regardless of the time since cancer diagnosis, but more marked in some patient groups. This information may assist health professionals improve cancer survivors' health and well-being. Abstract: Background: With the prevalence of cancer survivors increasing, their unique needs must be better understood. We examined the health, lifestyles and social circumstances of adults with and without a history of cancer. Methods: We performed a cross-sectional study, using exposure and outcome data from the baseline survey (2006–2009) of participants in the 45 and Up Study, a prospective cohort study in New South Wales, Australia. We compared 20, 811 cancer registry-verified adult cancer survivors with 207, 148 participants without a history of cancer using propensity score weighting and accounting for multiple testing. The propensity weighting included age, sociodemographic factors and number of self-reported co-morbidities. Results: Cancer survivors were more likely to report poorer physical and psychological health and quality of life compared to those without a cancer history, with most deficits still evident more than 10 years after cancer diagnosis. Cancer survivors were more likely to have a higher body mass index, but were less likely to smoke. Cancer survivors had greater functional limitations, including sexual, and were less likely to work full time, volunteer and spend time outdoors. Their social connectedness was, however, similar. Those with haematological cancer, lung cancer, or distant metastases, and those diagnosed at an older age, had the greatest health deficits and functional limitations. Conclusions: A history of cancer is associated with poorer health and less paid and unpaid work. Our findings reinforce the importance of routine long-term, integrated multidisciplinary care for cancer survivors and indicate the subgroups with the greatest unmet needs.